Midnight in Washington : how we almost lost our democracy and still could - Schiff, Adam B. (Random House, 2021)
The congressman who led the first impeachment of Donald Trump, and who became the president's chief antagonist, presents an inside account of American democracy at its darkest hour and how its future is more uncertain than ever.